Investigating the Activities of CAF20 and ECM32 in the Regulation of PGM2 mRNA Translation - Mustafa Al-gafari; Sasi Kumar Jagadeesan; Thomas David Daniel Kazmirchuk; Sarah Takallou; Jiashu Wang; Maryam Hajikarimlou; Nishka Beersing Ramessur; Waleed Darwish; Calvin Bradbury-Jost; Houman Moteshareie; Kamaledin B. Said; Bahram Samanfar; et al. (Biology)
Translation is a fundamental process in biology, and understanding its mechanisms is crucial to comprehending cellular functions and diseases. The regulation of this process is closely linked to the structure of mRNA, as these regions prove vital to modulating translation efficiency and control. Thus, identifying and investigating these fundamental factors that influence the processing and unwinding of structured mRNAs would be of interest due to the widespread impact in various fields of biology. To this end, we employed a computational approach and identified genes that may be involved in the translation of structured mRNAs. The approach is based on the enrichment of interactions and co-expression of genes with those that are known to influence translation and helicase activity. The in silico prediction found CAF20 and ECM32 to be highly ranked candidates that may play a role in unwinding mRNA. The activities of neither CAF20 nor ECM32 have previously been linked to the translation of PGM2 mRNA or other structured mRNAs. Our follow-up investigations with these two genes provided evidence of their participation in the translation of PGM2 mRNA and several other synthetic structured mRNAs.